As disputas pelo palácio governamental catarinense : as oligarquias, os autoritários e a instrumentalização do nacionalismo - Moraes, Marcos Juvencio de (2012)
This paper studies the political-economic-cultural relationships of the Santa Catarina s elites. Our investigation pervades the First Republic, the period in which there was the formation of a complex tangle of political relationships, composed by oligarchic interests in pursuit of the conquest of state power. When we enter the 1930s, we see a new form of administration, composed primarily of state authoritarianism. Finally, we address the Estado Novo, which uses nationalization to build new cultural patterns, closely linked to political interests. The wire conductor that connects the three periods is the project of nationalization of the Ramos oligarchy. It was started in 1911 by patriarch, Vidal Ramos, it was reconfigured in 1930 (period in which two intervenors of Rio Grande do Sul ruled Santa Catarina) and it was reinterpreted and it was intensified during the Estado Novo, with Nereus Ramos. We will see that Ramos oligarchy was representative of the landowners, of the Luso-Brazilian ethnicity and of the nationalism, project used to weaken the German industrial political enemies. Furthermore, we find that the administrations of the first intervenors and the installation of authoritarianism were indispensable for the consolidation of the nationalist project